Hospitals Cusptomer e-loyalty: How The Role of e-service quality, e-recovery service quality and e-satisfaction ? - Syahril Syahril; Manorang Sihotang; Rastanto Hadinegoro; Eva Sulastri; Imbuh Rochmad; Yoyok Cahyono; Agus Purwanto (Faculty of Science and Technology University of Pramita Indonesia, 2022)
The results of this study are expected (1) For the scientific aspect, the results of this study are useful for enriching empirical findings regarding the issue of E-Satisfaction and E-Loyalty, it is hoped that conceptual foundations can be found that have methodological implications regarding the delivery of E-Satisfaction and E-Loyalty. (2) For practical purposes, the results of this study can reveal useful information for the provision of quality services on E-Service Quality, and (3) For further researchers, research can encourage further researchers to find other variables that have a dominant influence on E-Service Quality, Satisfaction and customer E-Loyalty. Management Information System and E-commerce where Hospitals have provided E-commerce facilities which include the use of information technology and product marketing. Where this research has the meaning that the current marketing management of Hospitals cannot be separated from the use of technology packaged in the form of E-commerce transactions. Hospitals that have done this can be superior or competitive compared to similar companies that still transact manually, however, such Electronic-based services must be able to satisfy customers by reducing complaints submitted by consumers.